DEVELOPMENT MODEL ENTREPRENEUR LEADERSHIP (CASE STUDIED ON TAKALAR DISTRO THE TRAINING HALL STUDENT) - Kamaruddin, Rahma; Ahsan Anwar (Jurnal Administrasi Negara, 2020)
Entering the increasingly competitive business world requires high creativity to have the ingenuity to tap into every business opportunity. The present creativity and innovation. So utilizing something to develop into and opportunity for a business. As a development, there are several entrepreneur development models such as, greater resource, accounting, finance, leadership and so on. The research methods used in this study are descriptive quality study methods. Data collection using interviews, observation and document study. There are five informants in this study. The results of this study showed the development model of entrepreneur leadership in the Takalar's blossary student capable of developing the skill obtained after the training, in terms of commitment to the opportunities and commitments of the source of the students of the Blk Takalar students are basically they can see and take advantage of any opportunities and able to encourage subordinates, creative thinking, enterpreneur leadership on students of BLK on the control of resources have a strong motivation and work according to SOP, Enterpreneur leadership on students of BLK has a realistic vision.